Funchie Cookies / Nor Hasmida Hussin - Hussin, Nor Hasmida
Funchie Cookies is a chocolate snack -based product food and beverage to give the satisfaction of customers. It is identifying the people want to eat cookies as their snacks and also for the family who those of you who like snacks in your spare time. Unlike other chocolate snack -based products, Frunchie uses Callebaut Chocolate, which is a high quality coco. Frunchie has 2 types namely Cookies & Berry and Berry Crunch. Cookies & Berry is perfect for those of you who like biscuits coated in melted chocolate. And Berry Crunch for those of you who like crunchiness when chewed. It is affordable price of product. It is also targeting children, family and student to buy this product. Frunchie Cookies marketing strategy is to emphasize the quality and price of product. It offers the affordable price because many people want to buy this product especially in Terengganu. Thus, I develop marketing strategy that gives attraction to buy Frunchie. The taste is delicious and the product id high quality. The management of Frunchie Cookies consists by Nor Hasmida binti Hussin. I create Facebook to expand my business through social media and learn how to post Facebook post for business product whether teaser post, soft sell and hard sell. I must promote the product through the social media in Malaysia especially Terengganu. It also learns how to use eUsahawan Portal to record the sales. It is challenge for me to sell this product as my individual project.